Stimulus Enhancement: Controls for Social Facilitation and Local Enhancement - Heyes, C; Ray, E; Mitchell, C; Nokes, T (2000)
In two experiments, magazine-trained observer rats were given access to a pair of levers and allowed to make 50 reinforced responses immediately after the left or the right lever had been pressed 100 times for food reward by a conspecific demonstrator. In Experiment 1, where observers were rewarded for responses on either lever, those that had been able to see their demonstrators responding showed a response bias in favor of the demonstrator's lever, while rats that had been separated from their demonstrators by a metal screen did not. In Experiment 2, each observer saw a "viewed demonstrator" responding on one lever and was tested, with reinforcement for responses on the viewed demonstrator's lever or on the other manipulandum in a second chamber where a "box demonstrator" had just finished responding. Observers rewarded for responding on the same lever as the viewed demonstrator (Group SAME) showed better discrimination at the beginning of the test session than observers rewarded for responses on the other lever (Group DIFFERENT). Within Group SAME, rats whose box demonstrator had responded on the reinforced lever showed better discrimination than those whose box demonstrator responded on the nonreinforced lever, but the reverse was true in Group DIFFERENT. Both experiments provide evidence of stimulus enhancement unconfounded by social facilitation and local enhancement, and the latter suggests that demonstrator-deposited scent cues can facilitate discrimination via local enhancement or on the basis of their sensory properties alone. © 2000 Academic Press.